Estudo de variáveis de processo e da cinética de sinterização de materiais utilizados na produção de revestimentos cerâmicos - Santos, Cochiran Pereira dos (2016)
This study aims a reasoned study on the physical, chemical, mineralogical and microstructural characterization of four clay raw materials of the state of Sergipe, three of them never previously studied and evaluates its potential for use in the production of ceramic tiles. We analyzed the influence of process variables granulometry, pressing, ceramic formulation, heating rate and maximum firing temperature for the densification of the material. For this, the clays were characterized by X-ray diffraction, X-ray fluorescence spectroscopy, Fourier transform infrared spectroscopy, thermogravimetric and differential thermal analysis, particle size distribution, dilatometry, Atterberg limits, water absorption, modulus of rupture in bending and linear firing shrinkage. Calcite concentrations were detected between 1.1 and 13.7%, depending on the origin of the raw material. This information is crucial for adjustments in the firing cycle and predicts the minimum energy for the sintering occurs. The microstructure was investigated by scanning electron microscopy and from the results it was possible to confirm the correlation between the liquid phase formation and porosity reduction in the ceramic bodies sintered at 1150 °C. The determined activation energy in final sintering stage showed that, as it decreases the calcium carbonate content combined with the increase of flux material content, the sintering occurs at lower temperatures, resulting in lower energy costs in the process of production.